Evaluation of the hepatoprotective effect of an hydroalcoholic extract of Jatropha dioica against the damage induced by valproic acid in Wistar rats - Ramiro Tijerina-Márquez; Oscar H. Mendoza-Hernández; César B. Espinosa-Cantú; Verónica M Rivas-Galindo; Diana Moreno-Peña; Liliana Torres-González; Linda E. Muñoz-Espinosa; Edelmiro Pérez-Rodríguez; Idalia A. Cura-Esquivel; Paula Cordero-Pérez (Annals of Hepatology, 2024)
Introduction and Objectives: Liver diseases have gained importance due to their prevalence, incidence and because most chronic liver diseases have no cure, except for hepatitis C. Liver damage induced by drugs such as valproic acid (VPA) has been used to study therapeutic alternatives. Jatropha dioica may be one of these alternatives as it has metabolites with potential antioxidant activity. The objetive of this study was to evaluate the hepatoprotective effect of a hydroalcoholic extract of J. dioica against VPA-induced damage in Wistar rats. Materials and Patients: 24 Wistar rats of both sexes were used. Groups: Sham (SH), Non-Toxicity(JdTox), VPA and J. dioica+VPA(JdVPA) (n=6). J. dioica (300 mg/kg, p.o) was administered for 7 days, followed by VPA (500 mg/kg, i.p, for four days) injected concomitantly. Biochemical markers, oxidative stress, and histological analysis were determined. Ethics Committee approval under HI22-00003 registry and PAICYT 143-CS-2022 financing. The research group declares no conflict of interest. Results: VPA group showed a significant increase in ALT and AST against Sham, JdVPA group showed a significant decrease in these parameters vs. VPA (Figure 1), and the remaining biochemical markers showed no statistically significant differences between the groups. The VPA group presented statistically significant alterations in the concentrations of malondialdehyde (MDA), reduced glutathione (GSH), and superoxide dismutase (SOD) vs. SH. The JdVPA group significantly improved the damage caused by VPA, decreasing MDA and increasing GSH and SOD (Figure 2). Histologically, VPA presented an inflammatory infiltrate, which decreased in the JdVPA group. However, this difference was not statistically significant. Conclusions: In murine models, VPA has been able to induce alterations in transaminase levels and oxidative stress markers, both of which may indicate the presence of liver damage. Plants of the Jatropha genus have been shown to possess phenolic and flavonoid compounds with antioxidant capacity, which may be responsible for the hepatoprotective effect observed in this study using J. dioica at the evaluated dose without showing toxicity.